Potential of animal traction - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Guidelines for design production and testing animal-drawn carts by R A Dennis 1996 187pp price UKL 14.95 ISBN 1 85339 338 X